Development of an Interactive Multimedia E-Module Based on Everyday-Life Problems to Enhance Science Literacy Competence on the Digestive System - Yaqutunnafis, Siti Tsurayya; Prasetyo, Zuhdan (Jurnal Pendidikan Progresif, 2025)
Development of an Interactive Multimedia E-Module Based on Everyday-Life Problems to Enhance Science Literacy Competence on the Digestive System. Objectives: This research is motivated by the low level of scientific literacy among junior high school students and can have an impact on low critical thinking, motivation, and lack of awareness of scientific issues. Scientific literacy is one of the essential 21st-century skills that needs to be enhanced within the Merdeka Curriculum. This study aims to develop an e-module integrated with the Problem-Based Learning (PBL) model that is feasible, practical, and effective in improving students' scientific literacy. Methods: This research is an R&D research with ADDIE model. The research subjects involved 65 students who were divided into experimental & control classes, using random sampling techniques. Data collection was carried out through feasibility, practicality, and effectiveness tests, involving two expert lecturers, teachers, and students. Data collection techniques used PG science literacy test questions, and feasibility & practicality questionnaires which were analyzed descriptively, while effectiveness used N-Gain, Manova and effect size tests. Findings: The results of the study show that the developed interactive multimedia e-module was deemed feasible based on expert lecturer evaluations and received positive feedback from teachers. In terms of effectiveness, the improvement in students' scientific literacy achieved a high N-Gain score and a MANOVA result with a significance value greater than 0.05, while the effect size was 0.83. Conclusion: These findings indicate that the interactive multimedia e-module based on the Problem-Based Learning (PBL) model can effectively enhance students' scientific literacy. Keywords: problem based learning, e-module, science literacy.